1997
DOI: 10.1289/ehp.97105s3675
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between exposure to environmental estrogens and breast cancer?

Abstract: It was initially reported that levels of polychlorinated biphenyls (PCBs) 675-678 (1997)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…For example, occupational exposure to relatively high levels of DDT/DDE were not associated with an increased incidence of breast cancer [83] and even after 20 years of follow-up, exposure to relatively high concentrations of DDE showed no evidence of contributing to an increased risk of breast cancer [84]. Recent and past exposure to DDT did not play an important role in the etiology of breast cancer not even among women living in a country with a tropical climate in the North of Vietnam where insecticide use for mosquito control is common [85].…”
Section: Organochlorine Pesticidesmentioning
confidence: 98%
“…For example, occupational exposure to relatively high levels of DDT/DDE were not associated with an increased incidence of breast cancer [83] and even after 20 years of follow-up, exposure to relatively high concentrations of DDE showed no evidence of contributing to an increased risk of breast cancer [84]. Recent and past exposure to DDT did not play an important role in the etiology of breast cancer not even among women living in a country with a tropical climate in the North of Vietnam where insecticide use for mosquito control is common [85].…”
Section: Organochlorine Pesticidesmentioning
confidence: 98%
“…These compounds were used widely in industry for a wide variety of purposes, ranging from plastic resins to carbonless copy paper. Despite their utility, PCBs are linked to environmental and human health risks [32,33] that have resulted in the subsequent banning or highly restricted use of PCBs in many countries. However, it is estimated that >1 million tons of PCBs have been produced, and >70% of the PCBs made are still in use [34,35].…”
Section: Polychlorinated Biphenyls and Endometrial Cancermentioning
confidence: 99%
“…Environmental estrogen mimics are also implicated as endocrine disruptors in wildlife species. Although there is experimental evidence on the estrogenicity of several chlorinated pesticides (including DDT), as mentioned above, recent epidemiologic studies find no increased risk of breast cancer with pesticide exposure (102)(103)(104). Furthermore, in view of the presence of natural hormone and antihormone mimics in our diet, Safe and Zacharewski (105) concluded that the estrogenic contribution of organochlorine compounds is small and their role in development of breast cancer is questionable.…”
Section: Breast Cancer and Organochlorine Pollutantsmentioning
confidence: 99%